Cretaceous dinoflagellate cyst biostratigraphy in the Facai-1 well of the Tenere Graben in eastern Niger, Africa. (September 2020) - Liu, Jiguo; Cheng, Jinhui; Zhang, Guangya; Mao, Fengjun; Yang, Ning
Abstract: Sixty-five genera and 115 species of dinoflagellate cysts were discovered in the samples from the depth of 600–2652 m in the Facai-1 Well in the Tenere Graben of Niger, Africa. The low diversity and abundance in each single sample make it difficult to divide the dinoflagellate cyst assemblage into biozones. The dinoflagellate cyst assemblage is indicative of a Late Cretaceous age and suggests an abnormal neritic palaeoenvironment. Highlights: Dinoflagellate cysts were found in Facai-1 Well in Tenere Graben, Niger, Africa. Dinoflagellate cysts diversity looks high, but abundance is low. Geological age of dinoflagellate assemblage is the Late Cretaceous. Transgression happened, but the studied area was not a normal open sea.